2023
DOI: 10.3390/polym15102297
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Properties of Polyhedral Oligomeric Silsesquioxanes (POSS)-Based Epoxy Nanocomposites

Abstract: In this study, a tetrafunctional epoxy resin was loaded with 5 wt% of three different types of polyhedral oligomeric silsesquioxane (POSS) compounds, namely, DodecaPhenyl POSS (DPHPOSS), Epoxycyclohexyl POSS (ECPOSS), Glycidyl POSS (GPOSS), and 0.5 wt% of multi-walled carbon nanotubes (CNTs) in order to formulate multifunctional structural nanocomposites tailored for aeronautic and aerospace applications. This work aims to demonstrate how the skillful combination of desired properties, such as good electrical,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Owing to numerous advantages surpassing conventional materials like metals or ceramics [15,[100][101][102][103][104][105][106][107][108], epoxy composites are increasingly playing a primary role in the aeronautical and aerospace sectors. Some of their pivotal benefits include [109][110][111][112]:…”
Section: Thermal Stability Of Epoxy Composites Tailored For Aeronauti...mentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to numerous advantages surpassing conventional materials like metals or ceramics [15,[100][101][102][103][104][105][106][107][108], epoxy composites are increasingly playing a primary role in the aeronautical and aerospace sectors. Some of their pivotal benefits include [109][110][111][112]:…”
Section: Thermal Stability Of Epoxy Composites Tailored For Aeronauti...mentioning
confidence: 99%
“…Owing to numerous advantages surpassing conventional materials like metals or ceramics [ 15 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 ], epoxy composites are increasingly playing a primary role in the aeronautical and aerospace sectors. Some of their pivotal benefits include [ 109 , 110 , 111 , 112 ]: Exceptional strength-to-weight ratio, giving them a fusion of robustness and lightness, thus minimizing the overall weight and fuel consumption of aircrafts.…”
Section: Thermal Stability Of Epoxy Composites Tailored For Aeronauti...mentioning
confidence: 99%
“…Notably, even with a low amount of nanoparticles (0.1 wt%), the hybrid nanofiller concentration demonstrated a significant synergy, resulting in an increased cure degree for the hybrid epoxy samples compared to their single nanofiller counterparts, which had a higher percentage by weight (0.5 wt%) corresponding to the percentage above the EPT [6,9,39,40]. For instance, the sample EP 0.5% CNT exhibited a cure degree of 89% [41], while the sample EP 0.5% GN shows a cure degree of 86% [11]. In contrast, the unfilled resin EP exhibited a cure degree of 93% [41].…”
Section: Thermal Analysismentioning
confidence: 99%
“…For instance, the sample EP 0.5% CNT exhibited a cure degree of 89% [41], while the sample EP 0.5% GN shows a cure degree of 86% [11]. In contrast, the unfilled resin EP exhibited a cure degree of 93% [41]. This result is particularly important as it shows that even with the lowest weight percentage (0.1 wt%) of the nanofiller mixture, it is possible to obtain hybrid formulations with cure degrees meeting the requirements imposed by the aeronautical industries, with values close to or even exceeding those exhibited by binary formulations based on a single nanofiller, loaded with the higher weight percentage of 0.5 wt%.…”
Section: Thermal Analysismentioning
confidence: 99%
“…The results suggested that POSS had great potential to be used as a modifier to decrease the Dk and Df of CCLs, ensuring high-frequency and high-speed information transmission in communication. Furthermore, the flame-retardant performance of the POSS could be improved by introducing tunable side groups such as P-containing, N-containing, B-containing, or aromatic groups [ 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%